Small peptides induce antibodies with a sequence and structural requirement for binding antigen comparable to antibodies raised against the native protein. - Geysen, H M (1985)
Antisera were raised against the chemically synthesized peptide corresponding to each epitope of three foot-and-mouth disease virus strains. Peptide synthesis was further used to determine which amino acid residues in each epitope are important for the specificity of antisera raised against the whole virus. The specificity of the antibody paratope for its epitope was shown to depend on structure as well as sequence. Anti-virus sera demonstrated a greater specificity for the homologous peptide than did the anti-peptide sera. Two of the three peptides were able to induce neutralizing antibodies against the homologous virus. The specificities of the antibodies present in the anti-peptide sera were also inferred from the reactions of each with related sets of peptides. The cross-reactions observed for the anti-peptide sera were readily explained in terms of the antibody specificities determined to be present. The findings also suggest that the diversity of antibodies raised against small peptides is limited and is determined by the immune system. A similar limited response to the native protein was observed, which may account for the high frequency with which anti-peptide sera react with the native homologous protein.